An injectable scaffold based on crosslinked hyaluronic acid gel for tissue regeneration. Issue 20 (10th February 2016) - Yang, Rui; Tan, Linhua; Cen, Lian; Zhang, Zhibing
Abstract : An injectable scaffold of crosslinked hyaluronic acid gel for tissue regeneration. Abstract : Injectable scaffolds have great potential in specialised applications in regenerative medicine. In this study, hyaluronic acid hydrogels (HAGs) were prepared by crosslinking hyaluronic acid (HA) with 1, 4-butanediol diglycidyl ether (BDDE). Applications of HAG as an injectable scaffold for regenerating functional tissues were proposed by matching its viscoelastic properties with those of biological tissues. The effect of BDDE concentration on different properties of HAGs was explored. Swelling properties, cross-sectional morphology, and BDDE residues of the resulting gels were investigated. Rheological properties of different HAGs were measured by monitoring their storage modulus ( G ′) and loss modulus ( G ′′) and compared with those of biological tissues. It was shown that HAGs (BDDE from 0.4 vol% to 1.0 vol%) possess great water absorbing capability with swelling ratios ranging from 99.7 to 78.9. The higher the concentration of the crosslinker used, the more rigid the resulting hydrogel, subsequently the lower the swelling ratio would be and the higher the G ′ and G ′′ values as well. Similar viscoelastic behaviors were found between HAGs and biological tissues, such as epidermis, dermis, articular cartilage and tooth germ. SEM revealed that HAG obtained at 0.4 vol% BDDE had pore diameters ranging from a few microns to around 100 μm with a high degree of interconnectivity. The feasibility of this HAG, as an injectable scaffold, to regenerate cartilage and dentin–pulp complex was then demonstrated using a preliminary subcutaneous microenvironment. The current study could be a reference to take account of how a crosslinked HA gel should be chosen for specific tissue regeneration.